PENGEMBANGAN KOMIK INTERAKTIF UNTUK KETERAMPILAN MENULIS BAHASA ARAB PADA SISWA KELAS VI MI/SD ISLAM DI KOTA SEMARANG - Gunawan, Muhammad; Nafis Azmi Amrullah; Zukhaira (Universitas Negeri Semarang, 2024)
This research is a type of Research and Development (R&D) research using Sugiyono's model, which includes five stages, namely potential problems, data collection analysis, design, development, and evaluation. The research subjects included media expert validators, material experts, and Arabic language teachers. The data collection instruments consisted of questionnaires, observations, interviews, and documentation. The results showed that the interactive comic media for writing skills in Arabic for grade VI students of MI / SD Islam was “Very Feasible”, with the percentage of feasibility as follows: material feasibility 87.67, language feasibility 91.84, media feasibility 91.78, graphic feasibility 86.34, and typography feasibility 86.34, from all these feasibility interactive comic media for writing skills get a number 89 with the category “very feasible”. Therefore, it can be concluded that the Interactive Comic learning media for Writing Skills for Grade VI Students of MI / SD Islam in Semarang City is feasible to use in the learning process.